2001
DOI: 10.1021/ic010488k
|View full text |Cite
|
Sign up to set email alerts
|

Heterodi- [MAg, MAu (M = Pd, Pt)], Tri- [PdAg2, PtAg2, PtAu2, Pt2M (M = Ni, Pt, Cd, Hg)], and Tetranuclear (Pt2Ag2, Pt2Au2) 1,1-Ethylenedithiolato Complexes

Abstract: The reactions of [M(PPh(3))(2)[S(2)C=C[C(O)Me](2)]] [M = Pd (1a), Pt (1b)] with AgClO(4) and PPh(3) or with [Au(PPh(3))(OCMe(2))]ClO(4) afford heterodinuclear [[M(PPh(3))(2)][M'(PPh(3))][S(2)C=C[C(O)Me](2)]]ClO(4) [M = Pd, M' = Ag (2a), M = Pt, M' = Ag (2b), Au (4)] or trinuclear [[M(PPh(3))(2)][M'(PPh(3))](2)[S(2)C=C[C(O)Me](2)]](ClO(4))(2) [M = Pd, M' = Ag (3a), M = Pt, M' = Ag (3b), Au (5)] 1,1-ethylenedithiolato complexes, depending on the molar ratio of the reagents. We have recently reported that, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 71 publications
3
27
0
Order By: Relevance
“…Similar complexes with ruthenium or platinum have been described with different ligands. These complexes also contain S-Au-S units connected through aurophilic interactions in which the sulfur atoms are bonded both to gold and to the heterometal [283][284][285].…”
Section: Complexes With Bridging Bidentate Ligandsmentioning
confidence: 99%
“…Similar complexes with ruthenium or platinum have been described with different ligands. These complexes also contain S-Au-S units connected through aurophilic interactions in which the sulfur atoms are bonded both to gold and to the heterometal [283][284][285].…”
Section: Complexes With Bridging Bidentate Ligandsmentioning
confidence: 99%
“…The coexistence of such molecules is typical of the general class of distortion isomerism [29]. There are also nine derivatives [94,96,[120][121][122][123][124][125][126][127] which exist in two isomeric forms. These isomers differing from each other only by degree of distortion are also examples of distortion isomerism.…”
Section: Discussionmentioning
confidence: 99%
“…Vicente et al [22] have recently reported similar hetero di-, tri-, and tetra-nuclear Au-M systems (M = Pd, Pt Ni, Cd, Hg) by reacting [Au(PPh 3 )(OCMe 2 )]ClO 4 with these transition metal derivatives of S 2 C@C{C(O)Me}. However, aurophilicity was not invoked in these systems.…”
Section: Synthetic Schemementioning
confidence: 96%